THE ROLE OF DIGITAL MEDIA IN DEVELOPING CIVIC LITERACY AMONG HIGH SCHOOL STUDENTS IN THE ERA OF SOCIAL TRANSFORMATION - Sheik Mohamed S.H; Sam Hermansyah (SMART: Journal of Multidisciplinary Educational, 2024)
This study aims to explore the role of digital media in fostering civic literacy among high school students in the context of ongoing social transformation. As youth increasingly engage with digital platforms, this research seeks to understand how these technologies can be pedagogically leveraged to enhance students’ civic knowledge, critical thinking, and participatory skills. Employing a structured literature review as the primary method, the study systematically analyzes scholarly sources published between 2020 and 2025 to synthesize findings on the intersection of digital literacy and civic education. Results reveal that digital media—when used with intentional pedagogical design—can significantly improve civic awareness, ethical reasoning, and active engagement among students. However, disparities in access, teacher readiness, and curriculum integration remain persistent challenges. The novelty of this study lies in its integrated approach: positioning digital media not merely as a technological tool, but as a civic space that requires guided participation and critical engagement. It also contributes methodologically by offering a thematic synthesis of recent empirical findings specific to high school learners, a group often overlooked in digital citizenship discourse. The study concludes that fostering meaningful digital citizenship requires more than digital access; it demands targeted strategies that align media use with civic goals. Findings from this research are expected to inform educators, policymakers, and curriculum developers in designing inclusive and transformative civic education models suitable for 21st-century learners.